Enhancing ESG Through Gender Diversity and Family Involvement - Winarsih Herafni; Cynthia Afriani Utama (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of board gender diversity (BGD) on Environmental, Social, and Governance (ESG) performance in publicly listed Indonesian companies from 2017 to 2023. Growing global climate concerns and the increasing non-financial evaluation of companies necessitate an understanding of factors driving ESG performance. This research addresses whether BGD positively impacts ESG performance and if family relationships moderate this effect in Indonesian firms. Employing the System Generalized Method of Moments (System GMM) on panel data, the research addresses potential endogeneity, autocorrelation, and heteroskedasticity, acknowledging that past ESG performance influences current performance. The findings reveal a significant positive impact of overall BGD on aggregate ESG scores. However, BGD's effect on Environmental and Social performance is not statistically significant, while it significantly enhances Governance performance. The study also finds that family relationships do not significantly moderate the relationship between BGD and ESG performance. This suggests that BGD's positive influence on sustainability is consistent across family and non-family firms. The research underscores BGD's importance in corporate sustainability, but highlights nuanced internal company conditions and ownership structures that may affect the realization of women's independent contributions in strategic decision-making.